Digital and clinical approach to quantifying periodontal tissue changes after crown lengthening surgery: A case series pilot study - Goh, Rayner; Smith, Samantha Caitlin; Atieh, Momen; Tawse-Smith, Andrew (IIUM Journal of Orofacial and Health Sciences, 2023)
Crown lengthening surgery is a common periodontal procedure carried out to increase the amount of tooth exposure for aesthetic or restorative purposes. It is crucial for clinicians to understand the effect of crown lengthening surgery on the periodontal tissues to prevent relapse or over treatment. Even though various clinical parameters have been used by researchers in the past to quantify the amount of suprastructure exposed, the use of digital technology has not been widely adopted. The aim of this case series was to evaluate the changes in periodontal tissue after crown lengthening surgery with both clinical and digital approaches. This case series included five patients who underwent surgery at the Postgraduate Periodontics Clinic at the University of Otago over the period of six months. Clinical parameters such as probing depth, gingival recession, keratinised tissue height, plaque accumulation, gingival inflammation, crown height, gingival phenotype, and bone height were measured with a customised probing stent at baseline and 1-, 3-, and 6-month post-surgery. Digital impressions were also taken along with the clinical parameters to measure the volumetric changes. Most significant changes were observed in crown exposure, gingival recession and bone levels, followed by probing depth reduction for treated sites. Minimal changes were seen for the width of keratinised tissues, plaque levels and gingival scores. Volumetric changes were only significantly reduced after 6 months of healing. This case series found that crown lengthening resulted in an increase in tooth exposure and a reduction in tissue volume. Volumetric changes measured through sequential digital impressions were also comparable to clinical findings.